(3cfR GdCSeGA aj af GdeYeGs - (3bWH GdOjf eMeO Hf YdGA GdOjf CMeO Hf TeS GdOjf GdMfajs ((3Ydi Hf eMeO GdedGM s)
(3ChdgG (B:s
(3Chd eG jfWb Hg GddSGf CeG HYO adeG cGf ddCOH WQGFb WQGFa ESJNQL WGFaI ef COHGA GdYLe afGSehg GdeYfG hGHJcQhG ajg GdNjGdGJ GdObjbI dESJNQGL GdCSeG hUfYhG ajg GdJUGfja s
(3BNQgG (B:s
(3GdNGJeI ai GdYed GdJPjjdi hgh ef eMSfGJ Gdaf dGef VQhQjGJg hgPG BNQ eG JPcQJg GdCf ef GdeYejGJ djfJaY Hg Cgd GdCPhGb GdSdjeI ef WGdHi GdceGdGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1513s
Keywords: (3GdCOHs